Firm dynamics in retail trade: The response of Canadian retailers to exchange rate shocks - Jen Baggs; Eugene Beaulieu; Loretta Fung; Beverly Lapham (Queen's University, Department of Economics, 2015)
We use comprehensive firm-level data to estimate the responses of heterogeneous Canadian retail firms to real exchange rate movements. Our analysis focuses on a period characterized by large fluctuations in the Canadian dollar, providing an opportunity to quantify both intensive and extensive margin responses in retail industries to real exchange rate shocks and to examine how those responses differ across firms, locations, and sub-industries. Our results indicate that a real Canadian currency appreciation significantly reduces a retailer's sales, employment, and profits. The strength of this negative effect is decreasing in the distance of a retailer from the US-Canada border. We do not find evidence of a strong relationship between real exchange rate movements and the number of operating firms nor the probability of firm survival. These findings are consistent with the view that a real Canadian dollar appreciation increases cross-border shopping by Canadians, resulting in a negative demand shock for Canadian retailers, and the dominant response by firms to such a shock is through the intensive margin.
Keywords: F10; F14; L81; 330; Firm Dynamics; Retail Trade; Exchange Rates; Cross-border Shopping